Does dual plating clavicle fractures increase the risk of refracture after hardware removal?: a biomechanical investigation - Ruzbarsky, Joseph J.; Nolte, Philip-Christian; Miles, Jon W.; Tanghe, Kira K.; Nolte, Anna-Katharina; Hackett, Thomas R. (Journal of shoulder and elbow surgery, 2021)
Background - Dual orthogonal plating of midshaft clavicle fractures is increasingly used for osteosynthesis. The risk of refracture after hardware removal remains unknown. The purpose of this study was to compare the torsional and 3-point bending loads to failure of the clavicle following removal of single-plane, superior 3.5-mm plate fixation vs. dual orthogonal plating 2.7-mm constructs. - Methods - This study used 12 pairs of clavicles (N = 24) harvested from cadaveric specimens with a mean age at death of 56.5 years (range, 46-65 years). One clavicle from each pair was randomly assigned to either superior plating (SP, n = 12) or double plating (DP, n = 12). For SP, a superior 3.5-mm plate was used as a template to drill 3 bicortical 2.8-mm holes medial and lateral to the center of the clavicle. For DP, two 2.7-mm plates were used as a template to drill 4 bicortical 2.0-mm holes medial and lateral to the center of the clavicle. Clavicle pairs were randomly and evenly distributed to undergo either 3-point bending (n = 12) or posterior torsional loading (n = 12). Cyclic loading was performed, followed by load-to-failure testing. Stiffness, displacement at failure, load to failure, and failure mode were assessed and compared between SP and DP constructs. - Results - No significant differences between the SP and DP groups were observed for stiffness (768.2 ± 281.3 N/mm vs. 785.5 ± 315.0 N/mm, P = .872), displacement at failure (8.1 ± 2.8 mm vs. 5.4 ± 1.2 mm, P = .150), and ultimate load at failure (1831.0 ± 229.6 N vs. 1842.0 ± 662.4 N, P = .964) under the condition of 3-point bending. Similarly, no significant differences between the SP and DP groups were observed for torsional stiffness (1.3 ± 0.8 N · m/° vs. 1.1 ± 0.4 N · m/°, P = .844), rotation at failure (17.3° ± 4.4° vs. 14.4° ± 1.2°, P = .205), and ultimate torque at failure (14.8 ± 6.5 N · m vs. 14.7 ± 6.9 N · m, P = .103) under the condition of posterior torsional loading. The most common mode of failure for 3-point bending testing was an oblique fracture (7 of 12 clavicles, 58.3%), with no significant difference between groups (3 of 6 in SP group [50%] vs. 4 of 6 in DP group [66.7%], P > .999). The most common mode of failure with posterior torsional loading was a spiral fracture (10 of 12 clavicles, 83.3%), with no significant difference between groups (4 of 6 in SP group [66.7%] vs. 6 of 6 in DP group [100%], P = .455). - Conclusion - Following clavicle plate removal of either DP or SP, there is no statistically significant difference in the amount of force, under the condition of 3-point bending or torsional loading, required to fracture the diaphyseal clavicle in vitro.